PEMAKNAAN KHALAYAK TERHADAP KONSTRUKSI VAGINA DALAM IKLAN PRODUK FEMININE HYGIENE RESIK V - Naomi Putri Bahari Simeon; Hapsari Dwiningtyas S. (Interaksi Online, 2018)
This research was conducted to find out how the diversity of audiences interpretation to the construction of the vagina in the feminine hygiene product Resik V advertisement. The paradigm used is a critical paradigm with Stuart Hall's reception analysis method. In addition, in this research also uses structuralist semiotics analysis proposed by Roland Barthes through denotative and connotative meanings. Then, the main theory used is symbolic violence theory of Pierre Bordieu. This theory is to reveal symbolic violence to women in advertising. The results obtained that the informants in this research is able to give intrepetation towards vagina construction, but the meaning of the informants dominated by the ad ideology. The result of the interpretation of informant shows that there is diversity of meaningful position of audience that is dominant reading, negotiated reading, and opposisitional reading. This shows that the informants in this study are active audiences because they have the freedom to interpret messages in advertisements according to their own backgrounds. Media as the creator of the message can not govern what the audience thinks. The interpretation of the informants on vaginal construction in this research is influenced by various background factors such as gender, age, personal experience, and social environment. This research is not only to the limits of the informants interpretation only. It is precisely from the results of the interpretation of informants found that male informants tend to be more active in giving interpret to the construction of the vagina. Men know more about vaginal myths than women, because men often make the vagina an interesting topic of conversation. Meanwhile, women tend not to know their own vagina because in the research of women informants either married or single still tend to have the same meaning as the advertising dominant message. It shows that women do not realize that they are deceived by vaginal myths that are still in question. The powerlessness of women against the vaginal myths suggests that symbolic violence is not recognized by audiences.